FORMULASI MATRIKS TRANSDERMAL PENTAGAMAVUNON-0 DENGAN KOMBINASI POLIMER PVP K30 DAN HIDROKSIPROPIL METILSELULOSA - Beti Pudyastuti; Akhmad Kharis Nugroho; Sudibyo Martono (Sanata Dharma University, 2014)
Abstract: Transdermal delivery system is one of the delivery system for Pentagamavunon-0 (PGV-0) toavoid the high intensity of first pass metabolism of PGV-0 in peroral route. The purpose of this researchwas to optimize the formula of PGV-0 transdermal matrix with a combination of PVP K30 and HPMCpolymers.The simplex lattice optimization approach of the transdermal matrix formulas was performed byusing Design Expert 7.1.5 software. The visual appearance, weight, thickness, moisture content, moistureuptake, folding endurance, drug content, and dissolution efficiency of the release profil of PGV-0 from thematrix for 6 hours were evaluated as responses to determine optimum formula of matrix. The resultshowed that a combination of PVP K30 and HPMC polymers had a significant influence on the visualappearance, moisture content, and dissolution efficiency of PGV-0. Combination of 1.98% of PVP K30and 4.52% of HPMC as the optimum formula could produce homogeneous and flexible matrix withmoisture content of 3.21%. The dissolution efficiency was 9.11%, indicating that 101.93 g of PGV-0 wasreleased from the optimum formula during 6 hours.Keywords : Pentagamavunon-0, Transdermal matrix, PVP K30, HPMC